Pengaruh Pengetahuan Perpajakan Tarif Pajak dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak UMKM Wilayah Cikarang pada E-Commers di Shopee - Simanjuntak, Frangki Lasro Porman; Hartono, Hartono (Jurnal Pajak Vokasi (JUPASI), 2024)
The aim of this research is to analyze and evaluate the magnitude of the influence of tax knowledge (X1), tax rates (X2), and taxpayer awareness (X3) on Cikarang MSME taxpayer compliance in emmers on Shopee. The data used in this research is primary data obtained through distributing questionnaires to 100 respondents using the Slovin formula. The respondents are MSME taxpayers in the Cikarang area. The research approach used is a quantitative descriptive research approach. The sampling technique method is non-probability sampling and saturated sampling technique or census. Meanwhile, the data analysis used in this research includes: data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing with the help of the IBM SPSS application, showing that the variables of tax knowledge, tax rates and taxpayer awareness have a positive and significant effect, both in terms of partial or simultaneous, on taxpayer compliance. The tax compliance variable has a partial effect of 38.7% on MSME taxpayer compliance, the tax rate variable has a partial effect of 37.0% on MSME taxpayer compliance and the taxpayer awareness variable has a simultaneous effect of 42.7%. Based on the coefficient of determination, it is known that together tax knowledge, tax rates and taxpayer awareness have an influence on the dependent variable (MSME taxpayer compliance) by 63.5%, while the remaining 36.5% is influenced by other factors outside the research model. The implication of this research's conclusion is that the tax authorities or directorate general of taxes must increase tax knowledge, tax rates and taxpayer awareness to increase MSME taxpayer compliance.